Optimizing Human Capacity Development in Higher Education Institutions - Lidia Olga (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2023)
The presence and role of human resource management and lecturers are crucial factors in determining the efficiency and achievement of a college. In order to fulfill their professional responsibilities effectively and efficiently, lecturers must possess a range of essential attributes, including aptitude, motivation, self-regulation, dedication, adherence to workplace norms, and positive morale. The establishment of HR management schools highlights the recognition of the significant role human resources instructors play in influencing the reputation of graduates and the overall standard of higher education. This perspective is substantiated by the observation that faculty members wield significant authority within the academic realm, surpassing that of their counterparts in affiliated educational establishments. The relationship between training objectives and incentives is inherently interconnected. They mutually assist one another. The objective and rewards of training can be categorized into goals and benefits that satisfy both internal and external demands. The objective and advantages of training aimed at addressing internal demands encompass the alignment of training initiatives with the particular interests of human resources. The primary objective of training is to meet the needs of the external community, thereby contributing to the progress and growth of the institution. This has several advantages for the institution. The primary objective of lecturer development is to enhance knowledge, abilities, and attitudes pertaining to jobs or responsibilities within an organization, with the aim of attaining educational objectives and enhancing the overall quality of education.